Peran Resiliensi dalam Memediasi Pengaruh Budaya Manajemen Risiko Rantai Pasok terhadap Kinerja Organisasi - Ayra, Alisha Deeba; Santosa, Wahyuningsih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of Supply Chain Risk Management Culture on Re-engineering, Agility, Collaboration, and Organizational Performance. Based on research involving 125 respondents, it was found that Supply Chain Risk Management Culture positively and significantly influences Re-engineering, Agility, and Collaboration. However, these variables do not directly affect Organizational Performance. Instead, they act as mediators connecting the Supply Chain Risk Management Culture with improved Organizational Performance. Additionally, further research on 125 respondents in automotive companies in Bekasi City revealed that the implementation of Collaborative Supply Chain Management positively affects Operational Performance through enhanced Operational Capability. Strong collaboration between companies and business partners supports production efficiency, cost reduction, and product quality improvement. This study emphasizes the importance of Operational Capability as an intermediary in strengthening the relationship between Collaborative Supply Chain Management and Operational Performance. In conclusion, Supply Chain Risk Management Culture and Collaborative Supply Chain Management contribute to improving company performance through mediators such as Re-engineering, Agility, Collaboration, and Operational Capability. Companies are advised to continue developing culture and collaboration strategies to achieve efficiency and sustainable competitive advantages.